Self-Reported Giving-Way Episode During a Stepping-Down Task: Case Report of a Subject With an ACL-Deficient Knee - Houck, Jeff; Lerner, Amy; Gushue, David; Yack, H. John (The journal of orthopaedic and sports physical therapy, 2003)
Case report. To describe the knee kinematics and moments of a giving-way trial of a subject with an anterior-cruciate-ligament- (ACL) deficient knee relative to his non-giving-way trials and to healthy subjects during a step-down task. Episodes of giving way are believed to damage joint structures, therefore treatments aim to prevent giving-way episodes, yet few studies document giving-way events. The giving-way trial experienced by a 32-year-old male subject with ACL deficiency during a step-down task was compared to his non-giving-way trials (n = 5) and data from healthy subjects (n = 20). Position data collected at 60 Hz were combined with anthropometric data and ground reaction force data collected at 300 Hz to estimate knee displacement and 3-dimensional angles and net joint moments. The knee joint displacement was higher during the giving-way trial: from 4% to 32% of stance, reaching 9.0 mm at 18% of stance as compared to 1.6 +/- 0.7 mm for the non-giving-way trials. After 4% of stance, the knee flexion angle of the giving-way trial was 6.6 degrees higher than the non-giving-way trials and was associated with a higher knee extension moment. The knee frontal plane moment was near neutral during early stance of the giving-way trial in contrast to the non-giving way and healthy subjects which demonstrated a knee abduction moment. The response of this subject to the giving-way event suggests that higher knee flexion angles may enhance knee stability and, in reaction to the giving-way event, that knee extension moment may increase.